Luminescent SiO(2)-coated Gd(2)O(3):Eu(3+) nanorods/poly(styrene) nanocomposites by in situ polymerization - Macedo, Andreia G. (2010)
Europium doped gadolinium oxide nanorods have been coated with silica via a sol–gel approach. The silica coating increases the Eu3+ absolute emission quantum yields from 0.51 to 0.86 (255 nm excitation) and decay times from 1.43 to 1.80 ms (394.4 nm excitation). Subsequently the silica coating was modified with 3-(trimethoxysilyl)-propyl-methacrylate. Grafting of silica with the MPS coupling agent was confirmed by FTIR and contact angle measurements. The functionalized nanoparticles were used as core structures in the in situ radical polymerization of styrene via miniemulsion and solution routes. Depending on the polymerization technique used the morphology of the polymer coating consisted in isolated spheres or a homogenous film respectively. Although the optical properties of the ensuing nanocomposites were reduced the synthetic strategy developed to process this type of luminescent nanoparticles proved efficient and can be explored using different vinyl or (meth)acrylate monomers.